Knowledge Management Orientation: An Innovative Perspective to Hospital Management - Matina GHASEMI (Iranian Journal of Public Health, 2017)
Background: By considering innovation as a new project in hospitals, all the project management’s standard steps should be followed in execution. This study investigated the validation of a new set of measures in terms of providing a procedure for knowledge management-oriented innovation that enriches the hospital management system.